2000
DOI: 10.1095/biolreprod62.6.1526
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Culture on Imprinted H19 Expression in the Preimplantation Mouse Embryo1

Abstract: The H19 gene is imprinted with preferential expression from the maternal allele. The putative imprinting control region for this locus is hypermethylated on the repressed paternal allele. Although maternal-specific expression of H19 is observed in mouse blastocysts that develop in vivo, biallelic expression has been documented in embryos and embryonic stem cells experimentally manipulated by in vitro culture conditions. In this study the effect of culture on imprinted H19 expression and methylation was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
410
3
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 674 publications
(453 citation statements)
references
References 63 publications
(81 reference statements)
29
410
3
11
Order By: Relevance
“…In this study, the in vivo-produced blastocysts were different from the other blastocysts in that there was no time in culture. For example, previous studies have shown that epigenetic changes caused by in vitro preimplantation culture results in aberrant methylation and expression of a number of imprinted genes (Sasaki et al, 1995;Doherty et al, 2000;Mann et al, 2004). Further, the authors suggest that the epigenetic remodeling and reprogramming of the trophoblast may be more sensitive to the disruptive effect of the culture media than the ICM.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the in vivo-produced blastocysts were different from the other blastocysts in that there was no time in culture. For example, previous studies have shown that epigenetic changes caused by in vitro preimplantation culture results in aberrant methylation and expression of a number of imprinted genes (Sasaki et al, 1995;Doherty et al, 2000;Mann et al, 2004). Further, the authors suggest that the epigenetic remodeling and reprogramming of the trophoblast may be more sensitive to the disruptive effect of the culture media than the ICM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that nutritional availability around conception may affect the post-fertilisation wave of epigenetic reprogramming [36,37]. Multiple studies of embryos fertilised and cultured in vitro have suggested that imprinting control elements may be more susceptible to the environment during this period than previously thought [38,39]. However, these studies are potentially confounded by the effects of superovulation, which has been shown to alter the epigenetic status of maternal ICRs [40].…”
Section: The Role Of Imprinted Genes In Developmental Plasticity In Rmentioning
confidence: 99%
“…112 Of greater interest is that although culture of embryos to the blastocyst stage in KSOM maintains the appropriate maternal monoallelic expression of the imprinted H19 gene, H19 expression is essentially biallelic following culture in Whitten's medium. 113 Moreover, the loss of imprinting was associated with the loss of methylation on the paternal, repressed allele in the differentially methylated region (DMR); 113 DNA methylation of the paternal allele in this region is strongly linked with the repression of the paternal H19 allele. 114 The loss of imprinting that occurs during culture under certain conditions, as well as global changes in gene expression, could have long-term consequences on development.…”
Section: B Embryo Culture Results In Shifts In Energy Metabolismmentioning
confidence: 99%